"Führt die Jugend in die Geschichte eures Volkes ein […]" — schoolbooks on Jewish history in nineteenth-century Germany. Issue 4 (2nd October 2022) - Hennig, Fabian
ABSTRACT: This paper will examine the role Jewish history textbooks have played in establishing narratives of Jewish history in nineteenth century Germany. Through reviews of textbooks on Jewish history and ensuing debates, certain narratives were established or discarded. Furthermore, the discussions will illuminate how Jewish history turned from a scholarly enterprise of an elite few, into the basis of identification with Judaism for many German Jews. Whilst the community of scholars (like Heinrich Graetz, I. M. Jost, Abraham Geiger, Markus Brann) of Jewish history was rather small, schoolbooks became parallel to historical novels as a main venue for the dissemination of knowledge of the Jewish past to the masses. Sixteen years after Jost's first volume Geschichte der Israeliten, the first German schoolbook on Jewish post-biblical history was published by rabbi Ephraim Willstätter. A wave of about 20 schoolbooks followed in the next decades. The discussions of these books show that Jewish educators pushed for positive and inspirational presentations of the Jewish past, explicitly analogous to school books on German history. This paper will argue that the changing historical consciousness that is often attributed to Graetz, was precluded and pushed for by Jewish educators.